2019
DOI: 10.1021/acs.orglett.9b03726
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Compatible Diazo-Transfer Reaction in Aqueous Media Suitable for DNA-Encoded Chemical Library Synthesis

Abstract: DNA-encoded chemical libraries (DECLs) are increasingly employed in hit discovery toward proteins of pharmaceutical interest. Protected amino acids are the most commonly used building blocks for the construction of DECLs; therefore, the expansion of reaction scope with the subsequent free amine is highly desired. Here, we developed a robust DNA-compatible diazo-transfer reaction using imidazole-1-sulfonyl azide tetrafluoroborate salt converting a wide range of primary amines into their corresponding azides in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…At the beginning, we compared our method to a similar method of Gironda-Martínez et al [24] (using no copper catalyst) and found excellent conversion for different chain lengths (≥95%, Entries 1-6 in Table 2). Only for the a-amino acid (Entry 2), comparable conversion to our protocol was observed and seemed to identify a potential limitation to the method without CuSO 4 as most of the examples without Cu had the amine activated either in the a-position to a carbonyl or in a benzylic position, whereas with copper no limitations were observed for primary amines.…”
Section: Determining the Scope For The Optimized Diazo Reaction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning, we compared our method to a similar method of Gironda-Martínez et al [24] (using no copper catalyst) and found excellent conversion for different chain lengths (≥95%, Entries 1-6 in Table 2). Only for the a-amino acid (Entry 2), comparable conversion to our protocol was observed and seemed to identify a potential limitation to the method without CuSO 4 as most of the examples without Cu had the amine activated either in the a-position to a carbonyl or in a benzylic position, whereas with copper no limitations were observed for primary amines.…”
Section: Determining the Scope For The Optimized Diazo Reaction Conditionsmentioning
confidence: 99%
“…For more complex molecules, this transformation has been shown to work on solid phase [21], oligodeoxyribonucleotides [22], and proteins [23]. Recently, the work of Gironda-Martínez et al [24] showed that it was possible to generate azides selectively from the corresponding a-amino group within amino acids conjugated to DNA, via a diazo-transfer reaction, using the relatively safe imidazole-1-sulfonyl azide tetrafluoroborate salt. This method was developed to proceed without copper as a catalyst as the copper could potentially cause DNA-damage.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an oligonucleotide bearing a terminal amino linker underwent a peptide coupling first with a corresponding glycine as a proof of concept, then with a variety of amino-acids or alkyle derivatives. The resulting free amino group was later converted into an azide group through a diazo transfer with the popular and shelf-stable imidazole-1-sulfonyl azide salt [ 51 ]. A Staudinger ligation was nicely designed onto a post-synthesis azide-labeled ODN to introduce a fluorescent dye bearing a triphenylphosphine group [ 52 ].…”
Section: Chemical Strategies For Post-synthetic Functionalizationmentioning
confidence: 99%
“…[7] Several DNAencoded libraries with different molecular designs have been proposed and a growing number of chemical reactions are being explored in order to enable DNA-compatible assembling of building blocks. [8][9][10][11][12] Chemical moieties can be covalently attached on a single DNA strand (i. e., single-pharmacophore libraries) or at the extremities of two individual complementary DNA strands (i. e., dual-pharmacophore libraries). [13][14][15][16] Dual pharmacophore libraries can be particularly useful in the discovery of synergistic pairs of fragments that simultaneously bind to two adjacent sites on the protein surface, benefiting from the chelate effect.…”
Section: Introductionmentioning
confidence: 99%